MOBILITY AS A COMPONENT OF PERSPECTIVE OF MODERN EDUCATIONAL PROCESS - Larysa L. Familiarska (Інформаційні технології і засоби навчання, 2014)
This article is devoted to the prospects of new approaches to training and retraining system of postgraduate education from the perspective of the concept of «mobility», which is due to the dynamic development of the modern world, information and communication technologies.In the article it is suggested interpretation of the term «computer-mobile devices», summarizing the characteristics of mobile agents, as well as investigated teachers’ attitudes to their use as a part of the pedagogical process. The prospects of the use of computer-mobile devices in education, as well as some aspects of the organization of training with their functionality are determined.